Dispute resolution in electronic commerce - Zhao, Yun (Studies and materials on the settlement of international disputes ;, 2005)
The rapid development of electronic commerce has given rise to a new generation of commercial practices and the need to address the issue of resolving disputes arising out of such practices; only recently has attention been paid to this area. The issue of dispute resolution is extremely important because the dispute mechanism used will largely influence the attitudes of merchants and consumers at large, which will in turn determine the fate of electronic commerce. This issue has been discussed at various forums, however, no book has yet been published on the above topic. The present book provides a comprehensive analysis of the law and practice relevant to dispute resolution in electronic commerce. Anyone interested in E-commerce Law or dispute resolution, or conducting business over the Internet will find this book particularly useful.